ผลกระทบของธรรมนูญกรุงโรมว่าด้วยศาลอาญาระหว่างประเทศต่อรัฐและคนชาติของรัฐที่ไม่เป็นภาคี : ศึกษากรณีประเทศไทย - รินทร์ธิยา เธียรธิติกุล (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
This thesis aims at studying on principles of international law in the prospect of countries that are bound to the Rome Statute of International Criminal Court, focusing on signatory states and non-party states including Thailand as a signatory state. The purpose of Rome Statute is to bring criminals committing grave crime in international communities to justice by accepting no immunity. This is to protect or to remedy the injured person. Consequently, the International Criminal Court has specified principles of jurisdiction practicing in those states. The study found that the enforcement Rome Statute had the impact to the states and national of signatory states, including Thailand and her citizens. The case may be under the Court jurisdiction if the United Nations security Council delivered the case to the International Criminal Court without the consent of that state or the crime is committed in the territory of party state or the court jurisdiction is accepted. Therefore, if Thailand will ratify the RomeStatute in the future, she will need to review the laws in order to comply with the possible abligations to enable Thai courts to prosecute criminals or to express the objection against the Court jurisdiction or the acceptance of case by the Court. Also, the ratification of Rome Statute affects Thais because the Court has an absent immunity to everyone. Hence, the King, the military personnel or the operative officers may probably be affected by the Rome Statute as well. Thus, Thailand should consider the possible consequences from being signatory state and party state if the ratification is given in the future.